STRATEGIES FOR DEVELOPING MICRO, SMALL AND MEDIUM ENTERPRISES IN SUPPORTING SUSTAINABLE TOURISM IN BANGLI REGENCY, BALI PROVINCE - I Made Kartika; Nyoman Dwika Ayu Amrita; I Dewa Gede Putra Sedana; Made Mulia Handayani (RADJA PUBLIKA, 2025)
Tourism is a development sector that can support economic equality. MSMEs play a crucial role in supporting sustainable tourism in Bangli Regency, Bali Province, as they provide tourism needs. The purpose of this research is to:to formulate a strategy for developing MSMEs in Bangli Regency by identifying strengths, vulnerabilities, opportunities and threats (SWOT).This research utilizes a descriptive qualitative approach to describe phenomena relevant to the issue under study. Interviews were used as the data collection method, while descriptive analysis and SWOT analysis were used for analysis.Research findings include: 1) The development of craft MSMEs has strengths in the form of uniqueness based on local culture, support from nature and tradition, as well as government support and raw materials, as well as opportunities in the form of tourism trends, policy support, digital technology, and collaboration. However, there are weaknesses in design innovation, market access, utilization of digital technology, and managerial capacity, as well as threats in the form of competition, counterfeit products, and dependence on tourists; 2) Craft MSMEs are in a strategic position to strengthen competitiveness through capacity building and product innovation programs, digital marketing, strengthening partnerships, access to financing, local product campaigns, and strengthening distribution infrastructure.